2014
DOI: 10.1007/s00170-014-6645-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cutting conditions on the milling process of titanium alloy Ti6Al4V

Abstract: Titanium alloy is a difficult-to-cut material, widely used due to its excellent material and mechanical properties. In this paper, the cutting mechanisms of titanium alloy Ti6Al4V under up-milling and down-milling with different cutting conditions have been theoretically and experimentally discussed. The milling processes were simulated by an orthogonal cutting finite element model. And a series of milling experiments were carried out to verify the simulated results. Significantly, it elaborates the prominent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 26 publications
(26 reference statements)
1
26
0
Order By: Relevance
“…Regarding the comparison of up-milling and down-milling strategies, the average values show higher values in case of up-milling, which seems to indicate that the down-milling strategy is slightly more favorable from the point of view of torque. This difference is not statistically significant given the variance observed in the analyzed sample, so considerations on the quality of the surface and other offered for the machining of these alloys manufactured by conventional technologies could be considered in this case [25]. Figure 11 shows the torque values during the cutting test at a cutting speed equal to 50 m/min and a speed of 60 m/min.…”
Section: Torque Analysis During Cutting Paw-waam Wallsmentioning
confidence: 98%
“…Regarding the comparison of up-milling and down-milling strategies, the average values show higher values in case of up-milling, which seems to indicate that the down-milling strategy is slightly more favorable from the point of view of torque. This difference is not statistically significant given the variance observed in the analyzed sample, so considerations on the quality of the surface and other offered for the machining of these alloys manufactured by conventional technologies could be considered in this case [25]. Figure 11 shows the torque values during the cutting test at a cutting speed equal to 50 m/min and a speed of 60 m/min.…”
Section: Torque Analysis During Cutting Paw-waam Wallsmentioning
confidence: 98%
“…Johnson and Cook [23] presented a constitutive model which describes the flow stress of materials considering the effects of strain, strain rate, and temperature, and it is very suitable to express the deformation behavior of metals under high strain rate and temperature. This model is widely used as a constitutive equation in machining simulation by many researchers [24][25][26][27][28][29][30], and is often established by the SHPB tests [31][32][33][34][35][36][37]. Wu and Zhang [24] used the Johnson-Cook (J-C) equation as the constitutive model of Ti6Al4V alloy to investigate the milling process using the finite element method.…”
Section: Introductionmentioning
confidence: 99%
“…This model is widely used as a constitutive equation in machining simulation by many researchers [24][25][26][27][28][29][30], and is often established by the SHPB tests [31][32][33][34][35][36][37]. Wu and Zhang [24] used the Johnson-Cook (J-C) equation as the constitutive model of Ti6Al4V alloy to investigate the milling process using the finite element method. Umbrello et al [25] studied the effects of J-C constitutive parameters of AISI 316L in an orthogonal cutting simulation on cutting force, chip formation, temperature distribution, and residual stress.…”
Section: Introductionmentioning
confidence: 99%
“…It was concluded that there is a significant difference between UM and DM operations in terms of the hardness of the treated surface, and that the operation DM in the final passage can be used to increase surface hardness. Wu et al [9] were engaged in experimental research and simulation process at UM and DM of titanium alloy Ti6Al4V (high strength, excellent fracture resistance, and corrosion resistance) difficult for machining. Tool material was TiAlN-coated carbide, tool diameter 10 mm.…”
Section: Introductionmentioning
confidence: 99%